'Oh, This Is More of Stretch's Show': Randal Stretch and Puppet Theatre in Eighteenth-Century Ireland. (1st September 2022) - MOLONY, MARTIN G.
Abstract : This article outlines the popularity – and financial success – of an eighteenth-century Dublin puppet theatre that threatened mainstream theatres of the time. Randall Stretch's puppet theatre, in Dublin's Capel Street, became the centrepiece for satirical and political commentary of the day. Stretch's theatre caught the attention of Dean Swift and his circle and is commemorated in satirical verse of the period. For decades, Dubliners used the phrase 'This is more of Stretch's Show' to refer to anything outlandish or incredible. The article underlines the power of the puppet theatre as a satirical device and the extent to which it can rival mainstream theatre.